MIGRATION PROCESSES AS A FACTOR IN THE FORMATION OF ETHNO-NATIONAL IDENTITY IN THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article examines migration processes in the Kyrgyz Republic as one of the key factors in the formation and transformation of ethno-national identity in the context of post-Soviet transformations and globalization. Based on statistical data from the National Statistical Committee of the Kyrgyz Republic, materials from international organizations (UN, IOM), as well as studies by domestic and foreign scholars, the main trends of internal and external migration and their impact on the ethno-demographic structure of society are identified. Particular attention is paid to the socio-cultural and political consequences and challenges of migration, including issues of interethnic interaction, preservation of ethno-cultural identity, and the integration of migrants into the host society. The study employs systemic, structural-functional, and comparative methods, as well as elements of statistical and institutional approaches. The scientific novelty of the research lies in a comprehensive interpretation of migration not only as a socio-economic phenomenon but also as a significant factor in the formation of ethno-national identity in the contemporary Kyrgyz Republic.
Keywords: migration processes; ethno-national identity; internal migration; external migration; ethno-demographic structure; interethnic relations; Kyrgyz Republic